A Bot Approach-Based Capacity Testing Automation for Online Video Games - Sidiq, Adity M.; Husen, Jati H.; Widowati, Sri (Jurnal ELTIKOM : Jurnal Teknik Elektro, Teknologi Informasi dan Komputer, 2022)
Online games are a type of computer game that can be accessed using the internet network and played with other players to play the same game. With the advance in online game development, game developers are required to develop games that can be played by many players in one game, especially in the capacity of an online game server. Those needs can be achieved by utilizing bots. However, previous works only conducted bot-based testing for testing network capabilities. In this research, those works will be extended further ftotesting the capacity of a game server. The result of this research suggests that bot approach testing can simulate real players adequately. Other than that, the bot approach also can be scalable. However, the result also suggests that the bot approach still has some limitations as bots cannot simulate the dynamics shown by real players. Special attention is also needed towards clients utilized for executing the bots for them to be scalable.